Three - dimensional Numerical Simulation and Validation of Load-settlement Behaviour of a Pile Group under Compressive Loading - Gowthaman, S.; Nasvi, M.C.M. (The Institution of Engineers, Sri Lanka (IESL)., 2018)
Settlement of pile foundation is one of the controlling pile design parameters and its numerical simulation is one of the techniques widely used to predict the settlement behaviour of piles. This study was on the settlement behaviour of a pile group located in silty-sand deposits using the finite element (FE) approach which is based on the static pile load test. Three different types of analyses were investigated: (1) a linear elastic (LE) analysis in which the soil was assumed to be linear elastic, (2) a complete nonlinear analysis in which the soil adjacent to the pile shaft as well as the soil between the piles were modelled using the Mohr Coulomb (MC) or hardening soil (HS) model, and (3) a combined analysis in which the soil close to the pile shaft was modelled using the HS model while the soil in the remaining area was modelled using the LE or MC model. Numerical results obtained for the load-settlement behaviour of the pile group were validated using the popular RATZ analytical approach. The results of the FE analysis suggest that incorporating a nonlinear zone of soil close to the pile shaft as an interface and leaving the soil beyond this zone as linear elastic give a more reasonable estimation and a much better prediction of the pile group settlement. It is also suggested that for a typical pile group, a nonlinear interface of thickness equal to the pile diameter and extending from the pile shaft to the edge of the zone would be sufficient to capture the load transfer mechanism. The group settlement ratio predicted in this study is in good agreement with the findings made in the previous studies.
Keywords: Hardening-soil.; Interface.; Linear-elastic.; Mohr-coulomb.; Pile-group.; RATZ.; Settlement